2010
DOI: 10.1292/jvms.09-0341
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of CYP2C18 in the Cynomolgus Macaque (Macaca fascicularis)

Abstract: ABSTRACT. The macaque is widely used for investigation of drug metabolism due to its evolutionary closeness to the human. However, the genetic backgrounds of drug-metabolizing enzymes have not been fully investigated; therefore, identification and characterization of drug-metabolizing enzyme genes are important for understanding drug metabolism in this species. In this study, we isolated and characterized a novel cytochrome P450 2C18 (CYP2C18) cDNA in cynomolgus macaques. This cDNA was highly homologous (96%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…To determine the expression level of CYP2C93 mRNA relative to other CYP2C mRNAs, CYP2C93 mRNA, along with CYP2C8, CYP2C43, CYP2C75, and CYP2C76 mRNAs, was measured in the livers of two rhesus monkeys expressing CYP2C93 SV1. CYP2C18 mRNA was excluded from the analysis due to its hepatic expression level substantially lower than other CYP2C mRNAs [16]. The analysis indicated that the expression level of CYP2C93 mRNA was lower than that of any other CYP2C mRNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the expression level of CYP2C93 mRNA relative to other CYP2C mRNAs, CYP2C93 mRNA, along with CYP2C8, CYP2C43, CYP2C75, and CYP2C76 mRNAs, was measured in the livers of two rhesus monkeys expressing CYP2C93 SV1. CYP2C18 mRNA was excluded from the analysis due to its hepatic expression level substantially lower than other CYP2C mRNAs [16]. The analysis indicated that the expression level of CYP2C93 mRNA was lower than that of any other CYP2C mRNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The recombinant proteins of 19 cynomolgus P450s (CYP1A1, CYP1A2, CYP1D1, CYP2A23, CYP2A24, CYP2A26, CYP2B6, CYP2C18, CYP2C8, CYP2C9, CYP2C19, CYP2C76, CYP2D17, CYP2D44, CYP2E1, CYP2J2, CYP3A4, CYP3A5, or CYP3A43) were expressed in E. coli, and membrane preparations were performed as described previously (Uno et al, 2006(Uno et al, , 2007a(Uno et al, , 2009b(Uno et al, , 2010b(Uno et al, , 2011dUehara et al, 2010). For expression of cynomolgus CYP2J2 recombinant protein, the N-terminus modification was conducted by polymerase chain reaction with the forward and reverse primers, 5Ј-GGAATTC-CATATGGCTCTGTTATTAGCAGTTTTTGCGGCTGCCC TCTGGG-3Ј and 5Ј-GCTCTAGAGCAAAATCACACCCGAGGAAC-3Ј, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Cynomolgus CYP2C18 mRNA is expressed in the liver at a much lower level than other cynomolgus CYP2C mRNAs (Uno et al, 2010b). Cynomolgus CYP2C18 catalyzes S-mephenytoin 4′-hydroxylation (much less efficiently than human CYP2C19) (Table 3), but did not metabolize other human CYP2C substrates, such as paclitaxel or diclofenac (Uno et al, 2010b). Similarly, human CYP2C18 protein is a functional enzyme, that metabolizes human CYP2C substrates, but is not expressed, or is expressed at an undetectable level, in the liver (Gerbal-Chaloin et al, 2001).…”
Section: Cyp2c Subfamilymentioning
confidence: 96%
“…Cynomolgus CYP2C18 cDNA, 96% identical to human CYP2C18 cDNA, was recently identified (Uno et al, 2010b) (Table 1). Rhesus CYP2C18 cDNA, nearly identical to cynomolgus CYP2C18 cDNA, was found in GenBank (Table 2).…”
Section: Cyp2c Subfamilymentioning
confidence: 99%
See 1 more Smart Citation